Emergency endovascular management of acute thoracic aortic pathology A safe and feasible option. Issue 6 (December 2017) - Ahmed, Z.; McHugh, S.M.; Elmallah, A.; Colgan, M.P.; O'Callaghan, A.; O'Neill, S.M.; Madhavan, P.; Martin, Z.
Abstract: Endovascular repair has revolutionised the emergency treatment of thoracic aortic disease. We report our 10 year experience using this treatment in emergency cases. A prospectively maintained vascular database was analysed. Patients' medical records and CT images stored on the hospital PACS system were also reviewed. Statistical analysis was done using IBM SPSS V21. There were a total of 59 thoracic aortic stenting procedures of which 33 (60% males with a mean age of 58 yrs) were performed for emergency thoracic pathologies: traumatic transection (n = 10), ruptured aneurysm (n = 6), non-traumatic dissection (n = 8) and penetrating aortic ulcer (n = 9). All patients had self-expanding endografts implanted. Two patients required debranching procedures before the endovascular treatment. Thirty-day mortality was 12.1% (4/33). 70% of patients received a single device. There were 7 procedure related complications, 6 requiring re-intervention: thoracotomy and drainage in 2 patients, proximal graft extension in 2, open drainage of groin haematoma in 1 and open repair of a common femoral artery pseudo-aneurysm in one patient. In total 23 patients were transferred from 11 centres nationwide. There were no mortalities or other complications related to patient transfer from peripheral centres. Although acute thoracic aortic pathology is life threatening, appropriate blood pressure management and treatment of associated injuries can result in favourable outcomes. Endovascular repair is a safe and effective treatment option which enables patients to be treated with reduced morbidity and mortality. Transfer of patients with acute pathology to a tertiary centre can safely be performed.